Complicity in the Holocaust : churches and universities in Nazi Germany - Ericksen, Robert P. 1945- (Cambridge Univ. Press, 2012)
Robert Ericksen argues that enthusiasm for Hitler within churches and universities effectively gave Germans permission to participate in the Nazi regime